Assessment of intra-hepatic and intra-muscular lipid in obese pregnant women: an application of 3-tesla MRI. (7th June 2011) - Barr, S M; Cooper, A; Gray, C D; Semple, S; Norman, J E
Abstract : Background: Insulin resistance is exaggerated in both pregnancy and in obesity: obese pregnant women may display earlier onset or exaggerated insulin resistance which could contribute to some of the pregnant pathology associated with maternal obesity. The downstream consequences of insulin resistance include ectopic deposition of lipid in muscle and liver due to reduced lipid storage in adipose tissue. 3-Tesla (3T) MRI and spectroscopy techniques can be used to quantify intra-hepatic and skeletal muscle lipid content in non-pregnant individuals. Hypothesis: We hypothesize that: MRI techniques are suitable for quantifying organ lipid content in pregnant women. Obese pregnant women will have evidence of greater ectopic lipid deposition in liver and skeletal muscle compared with lean women. Approach: Healthy lean and obese women were imaged at approximately 36 weeks gestation in a 3T MRI scanner (Siemens). Spectroscopy data were obtained from a 2×2×2 cm voxel in quadriceps muscle. Images were also acquired of liver with water and fat signals both in and out of phase in order to calculate intrahepatic fat concentration. Results: Pilot data has been obtained from 6 women to date (lean n=4, obese n=2). Hepatic and skeletal muscle lipid content has been calculated. Intrahepatic lipid concentration ranges from 0.32 to 3.2%. Discussion: Preliminary data indicate that quantification of hepatic and skeletal muscle lipid content using this method is safe, practical and reliable and we believe that we are the first group in the UK to use such an approach in pregnant women.